Prevalence of Dental Caries Among Costa Rican Male Students Aged 12-22 Years Using ICDAS-II - Gudiño-Fernández, Sylvia (2021)
Objective: Dental decay is a public health challenge in Low- and Middle-Income Countries, particularly for young people, often confronted to healthcare access barriers. The aim of this study was to determine the prevalence and severity of dental caries among young male students in Costa Rica. Study design: A cross-sectional study was performed in 428 Costa Rican male students aged 12-22 years, who attended a nonprofit social welfare boarding school in 2019. A clinical examination was ran by three calibrated examiners following the International Caries Detection and Assessment System (ICDAS-II). Results: Caries prevalence was estimated at 83%, 15% have lost a tooth due to dental decay, 61% have at least one filled tooth, 36% have at least one filled and decayed tooth. The most frequent caries lesions were codes 2-Inactive (46.7%), and code 1-Inactive (23.8%). DMFT indicated a mean index using ICDAS-II 1-6>0 codes of 7.89. Using ICDAS-II 3-6>0 as threshold, the index decreases to 3.94. Finally, the lower and upper first permanent molars were found to be the most affected teeth. Conclusions: Dental caries experience represents a significant public health burden in young people, requiring better access to public dental healthcare.